HIV-1 VPU and VPR CTL epitope mapping by IFN-gamma elispot assay in HIV-1 infected Thai individuals with CD4+ count <= 300 cells/cb.mm. - Suthida Kerdsan (Chulalongkorn University, 2010)
Thesis (M.Sc.)--Chulalongkorn Univesity, 2002